2006
DOI: 10.1089/end.2006.20.569
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Renal Tumors: Intermediate-Term Results

Abstract: In the intermediate term (1-4 years), the oncologic effectiveness of RFA appears comparable to that of traditional treatments offered for small renal masses. Further studies of larger numbers of patients with longer follow-up are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 14 publications
5
68
0
3
Order By: Relevance
“…Nevertheless, the contribution of a confirmatory post-RFA biopsy to the diagnosis of the reccurrence can not be ignored in patients with suspected findings of recurrence on radiological analyses. In our follow up protocol including 3 rd and 6 th month controls, it was seen that no tumor (0%) reccurrences occurred, and this result was also in correlation with the literature (Gervais et al, 2005;Park et al, 2006;Zagoria et al, 2007;Ferakis et al, 2010;del Cura et al, 2010;Kim 2012). Although RFA is a less invasive treatment than surgical treatment options, various complications, such as pain, bleeding, hematuria, infection, urinary fistula, damage of adjacent structures can be occurred in RFA (Aron and Gill, 2005;Kwan and Matsumoto, 2007;Park et al, 2009;Ji et al, 2011;Atwell et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, the contribution of a confirmatory post-RFA biopsy to the diagnosis of the reccurrence can not be ignored in patients with suspected findings of recurrence on radiological analyses. In our follow up protocol including 3 rd and 6 th month controls, it was seen that no tumor (0%) reccurrences occurred, and this result was also in correlation with the literature (Gervais et al, 2005;Park et al, 2006;Zagoria et al, 2007;Ferakis et al, 2010;del Cura et al, 2010;Kim 2012). Although RFA is a less invasive treatment than surgical treatment options, various complications, such as pain, bleeding, hematuria, infection, urinary fistula, damage of adjacent structures can be occurred in RFA (Aron and Gill, 2005;Kwan and Matsumoto, 2007;Park et al, 2009;Ji et al, 2011;Atwell et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Median length of procedure was 7.5 hours (range [4][5][6][7][8][9][10][11][12][13][14]. Sixty percent (31/51) of cases utilized renal ischemia with hilar clamping with median time of 31 (range 8-136).…”
Section: Resultsmentioning
confidence: 99%
“…Early and intermediate outcomes for ablative therapies are encouraging, yet long-term results await. 11,12 Additionally, ablative technologies may not be technically possible, ineffective, or inadvisable for tumors located in close proximity to renal vessels or intimate with the collecting system. Furthermore, experience with ablative therapy in patients with hereditary kidney cancer is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported recurrence rates of less than 10% and excellent disease-specific survival rates of 95% to 100% in patients treated with thermal ablation. [42][43][44][45][46][47][48][49][50][51][52][53] Recent multiinstitutional reviews noted recurrent or residual disease in 3.9% to 5.2% of cryoablation patients and 12.9% to 13.4% in RFA patients. These numbers are difficult to compare, as significantly more patients had cryotherapy performed via laparoscopy and RFA was performed percutaneously.…”
Section: Thermal Ablation Therapies In Small Renal Massesmentioning
confidence: 99%